2008
DOI: 10.1021/jf801578x
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate Extracted from Ascidian Tunic Inhibits Phorbol Ester-Induced Expression of Inflammatory Factors VCAM-1 and COX-2 by Blocking NF-κB Activation in Mouse Skin

Abstract: Inflammatory factors are known to play a key role in promoting tumorigenesis; therefore, it is a promising strategy to inhibit the inflammation for cancer prevention. The current study was performed to investigate the potential effects of chondroitin sulfate (CS) extracted from ascidian tunic on the expression of inflammatory factors induced by treatment with 12- O-tetradecanoylphorbol-13-acetate (TPA) and to elucidate the underlying molecular mechanism of CS action in mouse skin inflammation. TPA was topicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…NFkB lies upstream of many inflammatory processes and has been implicated in several diseases, including inflammation-related cancers (39). The proposed mechanism of NFkB inhibition is additionally supported by studies which have demonstrated that glucosamine and chondroitin also inhibit inflammatory factors downstream of NFkB signaling, including IL-1β, IL-6, TNF-α, and PGE 2 , as well as COX-2 expression (8, 9, 38, 4042). These results hold in studies of glucosamine alone (8, 41), chondroitin alone (7, 38), and in studies of both supplements combined (43).…”
Section: Discussionmentioning
confidence: 85%
“…NFkB lies upstream of many inflammatory processes and has been implicated in several diseases, including inflammation-related cancers (39). The proposed mechanism of NFkB inhibition is additionally supported by studies which have demonstrated that glucosamine and chondroitin also inhibit inflammatory factors downstream of NFkB signaling, including IL-1β, IL-6, TNF-α, and PGE 2 , as well as COX-2 expression (8, 9, 38, 4042). These results hold in studies of glucosamine alone (8, 41), chondroitin alone (7, 38), and in studies of both supplements combined (43).…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, SC-FUC pretreatment could alleviate ethanol-induced histological damage, reverse changes in tissue oxidation and antioxidase activities, and regulate the signaling pathways of mitogen-activated protein kinases and matrix metalloproteinases [153]. Chondroitin sulfate isolated from ascidian Styela clava inhibited phorbol ester- and TNF-α-induced expression of inflammatory factors VCAM-1, COX-2 and iNOS by blocking Akt/NF-κB activation in mouse skin [154,155]. Anti-inflammatory activity of heparin analogues from ascidians and marine shrimps was also reported [156,157].…”
Section: Polysaccharides From Marine Animalsmentioning
confidence: 99%
“…Appleton et al [34] note that Kottamides A-D, bioactive alkaloids derived from the New Zealand ascidian Pycnoclavella kottae exhibits anti-inflammatory activity as revealed by analysis with 15N natural 2-D NMR. In addition, Xu et al [35] discovered that chondroitin sulfate extracted from Styela clava suppressed inflammatory factors and enhanced the effect of treatment with 12-O-tetradecanoylphorbol-13-acetate (TPA). As explained, anti-inflammatory properties are often discovered for tunicate compounds when testing for cytotoxicity or other characteristics.…”
Section: Anti-inflammatory Pathwaysmentioning
confidence: 99%